The Basel III Net Stable Funding Ratio and a Risk-Return Trade-Off: Bank-Level Evidence from Vietnam - Van Dan Dang, (Asian Academy of Management Journal of Accounting and Finance, 2021)
The Net Stable Funding Ratio (NSFR) liquidity rule under Basel III guidelines is designed to handle long-term liquidity risk, promoting the sustainable structures of bank funding. This study estimates the NSFR and analyses the impact of this liquidity ratio on banks according to a risk-return trade-off in Vietnam prior to the Basel III implementation. Using yearly data for commercial banks from 2007 to 2018, I find that banks with higher NSFR gain more potential benefits than banks with lower NSFR. Concretely, a rise in NSFR increases bank profitability and decreases bank funding costs, credit risks and liquidity creation, as evidenced by a comprehensive set of alternative measures. The findings of this study offer insightful implications on the bank policy framework advocating the Basel III liquidity regulation in Vietnam as well as other emerging markets.